2017
DOI: 10.1111/gwao.12208
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating for entitlement: Accessing parental leave in Hungarian firms

Abstract: There is a great deal of literature on the patterns and consequences of parental leave policies and on how and why certain countries adopted specific family policy clusters. Much less is known about the employment context that shapes workers' use of these policies. The current study focuses on the negotiation process that workers must undergo with employers regarding the length of leave and workers' ability to return to their jobs following leave. Given workers' increasing vulnerability in a global neoliberal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
(29 reference statements)
3
11
0
Order By: Relevance
“…They found that institutions did not always fully implement legislation or provide replacements for staff on maternity leave and that the legal protection for maternity leave could become in effect ‘an empty shell’. This echoes the findings of Fodor and Glass () with reference to the private sector in Hungary where parental and maternity leave provisions have become increasingly informal, individualized and subject to negotiation. Similarly, Byrne and Keher Dillon () research in the Irish context also highlighted the problem of informality in the management of maternity leave and the general failure of academic institutions to adapt to women's dual careers.…”
Section: Doing Gender In Academiasupporting
confidence: 85%
“…They found that institutions did not always fully implement legislation or provide replacements for staff on maternity leave and that the legal protection for maternity leave could become in effect ‘an empty shell’. This echoes the findings of Fodor and Glass () with reference to the private sector in Hungary where parental and maternity leave provisions have become increasingly informal, individualized and subject to negotiation. Similarly, Byrne and Keher Dillon () research in the Irish context also highlighted the problem of informality in the management of maternity leave and the general failure of academic institutions to adapt to women's dual careers.…”
Section: Doing Gender In Academiasupporting
confidence: 85%
“…It also justifies the critical position with the paternity leave system, both the current one and any extension proposal. The great similarities between these results and those provided by Fódor and Glass (2017) in the case of Hungarian mothers are noteworthy: their account also transforms the leave law into a "gift" dependent on the benevolence of employers. With the difference that because of their care-centered gender role, they are forced to accept it, in more or less negotiated terms, with the labor counterparts.…”
supporting
confidence: 59%
“…In addition, the workplace remains based on the norm of the 'ideal worker,' where workers are obligated to devote themselves to work without being free to consider caregiving desires and obligations (Burnett, Gattrell, Cooper, & Sparrow, 2013;Haas & Hwang, 2009;Hojgaard, 1997;Holter, 2007;Lewis & Stumbitz, 2017). The ideal worker norm can impact mothers' ability to take advantage of their statutory rights to parental leave (Fodor & Glass, 2017); Goldin (2014) also hypothesizes that the assumption that work hours cannot be flexible is responsible for the remaining gender gap in pay. In this special issue, we focus on how the ideal worker norm can also have a negative impact on men who want to be active fathers, since it discourages them from taking time off.…”
Section: The Potential Importance Of Workplace Supportmentioning
confidence: 99%